RANCANG BANGUN E-BOOK FISIKA BERBASIS EDUCATION FOR SUSTAINABLE DEVELOPMENT (ESD) BERORIENTASI KOMPETENSI SAINS PADA MATERI PEMANASAN GLOBAL - Felicia Amanda Putri; Winny Liliawati; Dedi Sasmita (PT. Hasba Edukasi Mandiri, 2026)
Scientific competence is an essential ability required of students to understand scientific phenomena, interpret science-based information, and apply it in decision-making in everyday life, particularly in the context of global issues such as climate change. However, various international studies, including the Programme for International Student Assessment (PISA), indicate that the level of scientific competence among Indonesian students remains relatively low. One contributing factor to this condition is the limited availability of contextual learning materials that are not yet integrated with sustainability issues. This study aims to develop a physics e-book based on Education for Sustainable Development (ESD), designed to support the enhancement of scientific competence on the topic of global warming. The study employs a Research and Development (R&D) method, which includes stages of needs analysis, product design, development, and limited trials. The feasibility of the e-book was evaluated through validation by subject-matter experts, media experts, and educational practitioners, while students’ responses were collected using questionnaires. The improvement in scientific competence was analyzed by comparing pretest and posttest results using N-gain calculations. The results indicate that the developed e-book meets feasibility criteria and receives positive responses from students. The e-book presents global warming material in a more systematic, contextual, and real world relevant manner. Therefore, the ESD-based physics e-book has the potential to be used as an alternative learning resource to support the development of students’ scientific competence.